Osteogenic efficacy of strontium hydroxyapatite micro-granules in osteoporotic rat model. (October 2016) - Chandran, Sunitha; Babu S, Suresh; VS, Hari Krishnan; Varma, HK; John, Annie
Excessive demineralization in osteoporotic bones impairs its self-regeneration potential following a defect/fracture and is of great concern among the aged population. In this context, implants with inherent osteogenic ability loaded with therapeutic ions like Strontium (Sr 2+ ) may bring forth promising outcomes. Micro-granular Strontium incorporated Hydroxyapatite scaffolds have been synthesized and in vivo osteogenic efficacy was evaluated in a long-term osteoporosis-induced aged (LOA) rat model. Micro-granules with improved surface area are anticipated to resorb faster and together with the inherent bioactive properties of Hydroxyapatite with the leaching of Strontium ions from the scaffold, osteoporotic bone healing may be promoted. Long-term osteoporosis-induced aged rat model was chosen to extrapolate the results to clinical osteoporotic condition in the aged. Micro-granular 10% Strontium incorporated Hydroxyapatite synthesized by wet precipitation method exhibited increased in vitro dissolution rate and inductively coupled plasma studies confirmed Strontium ion release of 0.01 mM, proving its therapeutic potential for osteoporotic applications. Wistar rats were induced to long-term osteoporosis-induced aged model by ovariectomy along with a prolonged induction period of 10 months. Thereafter, osteogenic efficacy of Strontium incorporated Hydroxyapatite micro-granules was evaluated in femoral bone defects in the long-term osteoporosis-induced aged model. Post eight weeks of implantation in vivo regeneration efficacy ratio was highest in the Strontium incorporated Hydroxyapatite implanted group (0.92 ± 0.04) compared to sham and Hydroxyapatite implanted group. Micro CT evaluation further substantiated the improved osteointegration of Strontium incorporated Hydroxyapatite implants from the density histograms. Thus, the therapeutical potential of micro-granular Strontium incorporated Hydroxyapatite scaffolds becomes relevant, especially as bone void fillers in osteoporotic cases of tumor resection or trauma.